Controlled manipulation of single atoms and small molecules using the scanning tunnelling microscope. Issue 9 (26th July 2013) - Morgenstern, Karina; Lorente, Nicolas; Rieder, Karl‐Heinz
<x xml:space="preserve">Abstract</x> This article reviews manipulation of single molecules by scanning tunnelling microscopes, in particular vertical manipulation, lateral manipulation, and inelastic electron tunnelling (IET) manipulation. For a better understanding of these processes, we shortly review imaging by scanning tunnelling microscopy – as a prerequisite to detect the manipulated species and to verify the result of the manipulation – as well as scanning tunnelling spectroscopy and IET spectroscopy which are used to chemically identify the molecules before and after the manipulation that employs the tunnelling current.